Planetary and Space Science - Planetary and Space Science (Elsevier, 2026)
Planetary and Space Science publishes original articles as well as short communications (letters). Ground-based and space-borne instrumentation and laboratory simulation of solar system processes are included. The following fields of planetary and solar system research are covered: Celestial mechanics, including dynamical evolution of the solar system, gravitational captures and resonances, relativistic effects, tracking and dynamics, cosmochemistry and origin, including all aspects of the formation and initial physical and chemical evolution of the solar system, terrestrial planets and satellites, including the physics of the interiors, geology and morphology of the surfaces, tectonics, mineralogy and dating, outer planets and satellites, including formation and evolution, remote sensing at all wavelengths and in situ measurements, planetary atmospheres, including formation and evolution, circulation and meteorology, boundary layers, remote sensing and laboratory simulation, planetary magnetospheres and ionospheres, including origin of magnetic fields, magnetospheric plasma and radiation belts, and their interaction with the sun, the solar wind and satellites, small bodies, dust and rings, including asteroids, comets and zodiacal light and their interaction with the solar radiation and the solar wind, exobiology, including origin of life, detection of planetary ecosystems and pre-biological phenomena in the solar system and laboratory simulations, extrasolar systems, including the detection and/or the detectability of exoplanets and planetary systems, their formation and evolution, the physical and chemical properties of the exoplanets, history of planetary and space research.
FI 0.46
Q3
Keywords: Earth; Space & Environmental Sciences; Space and Planetary Sciences; Ciencias espaciales y planetarias; Acuerdos transformativos; Transformative agreements; Planetas y satélites; Sistema solar; Cosmoquímica y origen